Verifique se (-1) e a raiz da equação 18x-6=6x
Soluções para a tarefa
Respondido por
1
Substituindo (-1) em x:
![18x-6=6x \\ \\ 18(-1)-6=6(-1) \\ \\ -18-6=-6 \\ \\ -18-6+6=0 \\ \\ -18=0 18x-6=6x \\ \\ 18(-1)-6=6(-1) \\ \\ -18-6=-6 \\ \\ -18-6+6=0 \\ \\ -18=0](https://tex.z-dn.net/?f=18x-6%3D6x+%5C%5C++%5C%5C+18%28-1%29-6%3D6%28-1%29+%5C%5C++%5C%5C+-18-6%3D-6+%5C%5C++%5C%5C+-18-6%2B6%3D0+%5C%5C++%5C%5C+-18%3D0)
Não verifica, portanto não é a raiz da equação.
Não verifica, portanto não é a raiz da equação.
Perguntas interessantes
Geografia,
11 meses atrás
Matemática,
11 meses atrás
Sociologia,
11 meses atrás
Matemática,
1 ano atrás
Geografia,
1 ano atrás
Matemática,
1 ano atrás
História,
1 ano atrás